The impact of ICT infrastructure on Malaysian trade - Ahmad, Nor Asma; Ismail, Normaz Wana; Law, Siong Hook (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2011)
This paper examines the impact of ICT infrastructure on trade in the case of Malaysia by using a gravity model and a number of indicators for the ICT infrastructure. The analyses are based on data from a panel of countries, 36 trading partner countries over time from 1980 to 2008. It is found that mobile and fixed-line telephone subscribers, personal computers and internet users are significant and positively related to the value of bilateral trade between Malaysia and its trading partners. The results support that infrastructure development serves as the facilitating role in reaching higher levels of exporting.